Matematyka
mati88123
2017-06-25 05:22:19
Potrzebuje rozwiazan od zadania 5 do 8. Daje najj;)
Odpowiedź
aga
2017-06-25 06:03:51

[latex]Zadanie 5. \ \ a) \ frac{x^2-9}{x^2+9x}=0 \ \ D: \ x^2+9x eq 0 \ x(x+9) eq 0 \ x eq 0 wedge x eq -9 \ \ x^2-9=0 \ (x-3)(x+3)=0 \ x=3 vee x=-3 \ \ Odp.: xin lbrace-3,3 brace[/latex] [latex]b) \ frac{x-4}{x-2}= frac{x-3}{x-4} \ \ D: \ x-2 eq 0 wedge x-4 eq 0 \ x eq 2 wedge x eq 4 \ \ (x-4)(x-4)=(x-2)(x-3) \ x^2-8x+16=x^2-5x+6 \ -3x=-10 \ x=3 frac{1}{3} \ \ Odp.: x=3 frac{1}{3} [/latex] [latex]c) \ frac{x-1}{x-4}=9-x \ \ D: \ x-4 eq 0 \ x eq 4 \ \ x-1=(9-x)(x-4) \ x-1=9x-36-x^2+4x \ x^2-12x+35=0 \ Delta=144-140=4, sqrt{Delta}=2 \ x_1= frac{12-2}{2}= 5 \ x_2= frac{12+2}{2}=7 \ \ Odp.: xin lbrace5,7 brace[/latex] [latex]d) \ frac{2-x}{x+3}=- frac{1}{5} \ \ D: \ x+3 eq 0 \ x eq -3 \ \ 2-x=-frac{1}{5}(x+3) \ 10-5x=-(x+3) \ 10-5x=-x-3 \ -4x=-13 \ x=frac{13}{4} \ x=3frac{1}{4} \ \ Odp.: x=3frac{1}{4} [/latex] [latex]e) \ frac{2-x}{x+3}=4 \ \ D: \ x+3 eq 0 \ x eq -3 \ \ 2-x=4(x+3) \ 2-x=4x+12 \ -5x=10 \ x=-2 \ \ Odp.: x=-2[/latex] [latex]f) \ frac{16-x}{(x+16)(x-16)}=0 \ \ D: \ x+16 eq 0 wedge x-16 eq 0 \ x eq -16 wedge x eq 16 \ \ 16-x=0 \ x=16 \ \ Odp.: xinemptyset[/latex] [latex]g) \ frac{(1-x^2)(x-3)}{x-1}=0 \ \ D: \ x-1 eq 0 \ x eq 1 \ \ (1-x^2)(x-3)=0 \ (1-x)(1+x)(x-3)=0 \ 1-x=0 vee 1+x=0 vee x-3=0 \ x=1 vee x=-1 vee x=3 \ \ Odp.:xinlbrace-1,3 brace[/latex] [latex]h) \ zobacz g)[/latex] [latex]i) \ frac{-3x-2}{4-5x}=0 \ \ D: \ 4-5x eq 0 \ x eq frac{4}{5} \ \ -3x-2=0 \ -3x=2 \ x=- frac{2}{3} \ \ Odp.: x=- frac{2}{3} [/latex] [latex]j) \ frac{-3x-2}{4-5x}-frac{2}{7}=0 \ \ D: \ 4-5x eq 0 \ x eq frac{4}{5} \ \ frac{-3x-2}{4-5x}=frac{2}{7} \ -3x-2=frac{2}{7}(4-5x) \ -21x-14=2(4-5x) \ -21x-14=8-10x \ -11x=22 \ x=-2 \ \ Odp.: x=-2[/latex] [latex]Zadanie 6. \ \ 6x^2y-2xy^2=2xy(3x-y) \ \ frac{2x-y}{3x-y}= frac{(2x-y)2xy}{(3x-y)2xy}= frac{4x^2y-2xy^2}{6x^2y-2xy^2} \ \ Odp.: frac{4x^2y-2xy^2}{6x^2y-2xy^2} [/latex] [latex]Zadanie 7. \ \ 2x^2+3xy=x(2x+3y) \ \ Odp.: x[/latex] [latex]Zadanie 8. \ \ frac{x^2+3x}{(x+3)^2} \ \ D: \ x+3 eq 0 \ x eq -3 \ \ frac{x^2+3x}{(x+3)^2}=frac{x(x+3)}{(x+3)^2}=frac{x}{x+3} \ \ frac{x}{x+3}=frac{-frac{1}{2}}{-frac{1}{2}+3}= frac{-frac{1}{2}}{frac{5}{2}}=-frac{1}{2}*frac{2}{5}=-frac{1}{5} \ \ Odp.: frac{x}{x+3}, -frac{1}{5}[/latex]

Dodaj swoją odpowiedź